Utilization of Seaweed (Eucheuma sp) as a Room Freshener Gel Product - Arham Yunus; Nurfiansyah Nurfiansyah; Alma Yasari; Fajrianthy; Jumriani Alimin; Rahmila; Halijah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
This study aimed to formulate a room freshener gel from seaweed (Eucheuma sp) with variations in acetic acid soaking concentrations (0%, 5%, and 10%) and to evaluate its physical characteristics. The seaweed-based gel was produced through soaking, heating, and molding processes combined with gelatin, isopropyl alcohol, and essential oils (lemon, sweet orange, and lily). Quality testing covered moisture content, viscosity, gel strength, and organoleptic properties. Results showed that the soaking treatment significantly affected gel quality. The unsoaked sample had the highest moisture content (24.08%), exceeding the SNI limit of 23.22%, while the 5% and 10% soaking treatments met the standard with moisture contents of 17.43% and 19.64%, respectively. Viscosity values ranged from 62,237 to 73,111 μm/pascal, all within the ideal range for semi-solid gels. Gel strength values of 85.859, 291.45, and 615.77 g/cm² for the three treatments all exceeded the minimum standard of ≥45 g/cm². Organoleptic evaluation by 20 panelists showed that the 5% acetic acid soaking treatment produced the best scores for aroma (3.70) and texture (4.25), meeting the SNI 01-2346-2006 acceptance threshold. This treatment is recommended as the optimal formulation for seaweed-based room freshener gel.